Transition Metal Catalyzed Reactions of Organomercurials-I: Palladium-Catalyzed Acyldemetallation and Cross-Coupling Reactions - More, P.G.; Desai, B.J. (Asian Journal of Chemistry, 2010)
The palladium catalyzed acyldemetallation and cross-coupling reactions of organomercurials are discussed. The acyldemetallation reaction provide a mild, selective and general method for the synthesis of unsymmetrical ketones in high yield. The palladium catalyzed cross-coupling reactions with organic halides proceed under mild conditions to give biaryles or arylated heterocyclic compounds in good yields. It is found that, nucleophilic catalysis (iodide ion) is an efficient method for activation of organomercurials in acyldemetallation and cross-coupling reactions.